1987
DOI: 10.1016/s0886-3350(87)80112-8
|View full text |Cite
|
Sign up to set email alerts
|

Organic tissue glue in the closure of cataract incisions

Abstract: We report our initial studies with a new organic tissue glue (Tisseel) in the closure of cataract incisions made in fresh cadaver eyes. We made two types of cataract incisions, posterior beveled and scleral pocket, and closed them with nylon sutures, glue, or a combination of both. The 11-mm posterior-beveled incision required eight nylon sutures, with or without glue, to maintain wound integrity at high intraocular pressures. We found the 7-mm and 11-mm pocket-type incisions to be essentially self-sealing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

1988
1988
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 4 publications
0
7
0
4
Order By: Relevance
“…Fibrin glue has been used in numerous studies for sealing cataract wounds [124][125][126][127][128][129]. Fibrin glue has also been used to assist in posterior chamber intraocular lens implantation in eyes with capsular support deficiency with good visual acuity outcome and no postoperative complications [130,131].…”
Section: Lens Surgerymentioning
confidence: 99%
“…Fibrin glue has been used in numerous studies for sealing cataract wounds [124][125][126][127][128][129]. Fibrin glue has also been used to assist in posterior chamber intraocular lens implantation in eyes with capsular support deficiency with good visual acuity outcome and no postoperative complications [130,131].…”
Section: Lens Surgerymentioning
confidence: 99%
“…Rosenthal et al 17 used a platelet/fibrinogen/thrombin mixture in lamellar keratoplasty in rabbits, and Buschmann 18 reported on the use of fibrin glue to close traumatic perforations of the anterior and posterior capsule. In the last 10 years, fibrin has been used to successfully close cataract incisions, 19 attach soft tissue in oculoplastic and strabismus surgery, 20 treat leaking blebs and close wounds in glaucoma surgery, 21,22 and treat corneal perforations. [23][24][25][26] The use of biologic glue as an adjunct to sutures in PKP has been previously described by Goins et al 27 Their study showed that photodynamic biologic tissue glue was comparable to sutures in providing adequate corneal wound strength in PKP in a cadaver eye model.…”
Section: Discussionmentioning
confidence: 99%
“…In 1998, Henrick et al used Tisseel fibrin to seal scleral pocket incisions without the need of additional sealants or sutures 68. While Mester et al demonstrated that the use of Tissucol fibrin (Baxter Hyland Immuno) reduced surgically induced astigmatism, Alio et al did not find any significant difference 69 70.…”
Section: Cataract Surgerymentioning
confidence: 99%